2007
DOI: 10.1161/01.atv.0000253907.51681.0e
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Plaque Characterization Using Intravascular Ultrasound–Virtual Histology in a Porcine Model of Complex Coronary Lesions

Abstract: Objective-To determine the accuracy of detection of different tissue types of intravascular ultrasound-virtual histology (IVUS-VH) in a porcine model of complex coronary lesions. Methods and Results-Coronary lesions were induced by injecting liposomes containing human oxidized low-density lipoprotein into the adventitia of the arteries. IVUS-VH imaging was performed in vivo at 8.2Ϯ1.6 weeks after injection. A total of 60 vascular lesions were analyzed and compared with their correspondent IVUS-VH images. Corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 27 publications
1
53
2
1
Order By: Relevance
“…A recent in vivo study using a porcine model reported that IVUS-VH was not accurate in detecting the area of each specific component within the corresponding histological specimen. 30 In the present study, neither the sensitivity nor the specificity of IVUS-VH in detecting different tissue types was as robust as validated in previous ex vivo studies. In our direct qualitative comparison, the overall agreement between the histological and IVUS-VH diagnoses was not as high ( =0.30) as in the quantitative comparison ( =0.73).…”
Section: Discrepancy Between Ivus-vh Findings and Histologycontrasting
confidence: 76%
See 1 more Smart Citation
“…A recent in vivo study using a porcine model reported that IVUS-VH was not accurate in detecting the area of each specific component within the corresponding histological specimen. 30 In the present study, neither the sensitivity nor the specificity of IVUS-VH in detecting different tissue types was as robust as validated in previous ex vivo studies. In our direct qualitative comparison, the overall agreement between the histological and IVUS-VH diagnoses was not as high ( =0.30) as in the quantitative comparison ( =0.73).…”
Section: Discrepancy Between Ivus-vh Findings and Histologycontrasting
confidence: 76%
“…This tendency is consistent with previously-reported results. 30 In contrast, good in-vivo diagnostic accuracy of IVUS-VH compared with histology has been reported, using tissue samples obtained by directional coronary atherectomy (DCA). 24 The reason for the discrepancy in diagnostic accuracy for tissue characterization may be explained as follows.…”
Section: Discrepancy Between Ivus-vh Findings and Histologymentioning
confidence: 99%
“…As described in many reports, it is possible that thrombus was present in the observation of regression of the PV in the acute phase because their discrimination is difficult on IVUS, and this might also have influenced the results. Moreover, the accuracy and reproducibility of identification of tissue properties on VH-IVUS might be uncertain 31 and this also requires further study. The study focused on the effects of statins over a short period, but long-term observation is necessary to judge the clinical efficacy.…”
Section: Study Limitationsmentioning
confidence: 99%
“…IVUS radiofrequency data analysis techniques for tissue characterization, namely VH-IVUS (20 MHz, phased-array transducer, Volcano Therapeutics), and iMap (40 MHz, mechanical-type transducer, Boston Scientific), have been developed as an extension to grayscale imaging [8]. However, the accuracy of VH-IVUS in complex lesions in a porcine model was limited [9,10]. Significant and systematic variability in plaque composition estimates was found in a study comparing VH-IVUS and iMap in vivo [11].…”
Section: Introductionmentioning
confidence: 99%